Role of Combined Mifepristone and Misoprostol Verses Misoprostol Alone in Induction of Labour in Patients with Intrauterine Foetal Death - a Randomized Comparison Between their Outcome - Abbasi, Sharmin; Siddiqua, Sehereen Farhad; Alam, Mohammad Noor A; Jesmin, Suha; Siddiqui, Md Mahmudur Rahman; Rahman, Md Tahminur (Anwer Khan Modern Medical College Journal, 2017)
Background: Intrauterine fetal death is means- intrapartum death after the fetus has reached the age of viability8. As in IUFD journey, labor pain will be fruitless. So, it is of utmost importance to search for the method which can reduce hours of pain in labor of IUFD cases. Metarials Methods: In this research work patients divided in two groups. Induction of labour in one group was given by combination of mifepristone and misoprostol other group by misoprostol only and we try to find out the best method. To compare the effectiveness, induction to delivery interval, safety and side effects of combination of mifepristone and misoprostol versus conventional use of misoprostol alone in induction of labour in patients with intrauterine fetal death. It is a Prospective randomized comparative study in Anwer Khan Modern Medical College Hospital and Dhaka Medical College Hospital among 70 patients with IUFD after 28 weeks of gestation during January 2014- January 2016. Result: We allowed the patients up to third gravid and after 28 weeks of gestation. Patients were grouped as Group A(35) & Group B (35). In Group A Induction was given by single oral dose of 200 mg mifepristone, and after 48 hours, tab. Misoprostol in post. fornix started if <34 weeks-100 ?gm dose and >34 weeks-50 ?gm dose. Doses were repeated every 6 hourly intervals if required. In Group B Induction was given by 100 ?gm misoprostol at 6 hourly interval in post. Fornix. In both groups we allowed misoprostol maximum 600 ?gm. Oxytocin was given for augmentation if needed. The two study groups did not differ demographically. Induction to delivery time was shorter with combined regimen group (P<0.001). Induction to delivery interval ranges from 10-12 hours in mifepristone plus misoprostole group.In only misoprostol group it was about 24-26 hours. Doses of misoprostol was lower in combined group (P<0.001). 4 patients need Oxytocin for augmentation in only misoprostol group. In combined group oxytocin was not needed. The two groups did not differ as regards complications experienced during labour and delivery significantly. In overall out come 2 failed induction in misoprostol only group but not in combinedgroup. Conclusion: In Induction of IUFD mifepriston plus misoprostol is an effective combined group. It is safe, non invasive, easily tolerable, highly cost effective, had less induction to delivery interval, required less dose of misoprostol and no need of augmentation with oxytocin. So,the combined group is more effective than conventional regimen of misoprostol alone. Anwer Khan Modern Medical College Journal Vol. 8, No. 1: Jan 2017, P 50-54